Incentive provision with hidden characteristics: A unified approach - Martin Hellwig (Max Planck Institute for Research on Collective Goods, 2006)
The paper develops a technique for studying incentive problems with unidimensional hidden characteristics. The technique supports a unified approach, which can be applied regardless of whether the type set is finite, the type distribution has a continuous density, or the type distribution has both, mass points and an atomless part. The proposition that optimal incentive schemes induce no distortion at the top and downward distortions below the top is confirmed for arbitrary type distributions. However, mass points are pooled with immediately neighbouring higher types. Between a mass point and immediately neighbouring lower types, there may have to be a discontinuity.
Keywords: C61; D82; D86; 330; Hidden Characteristics; with General Type Distributions; Principal-Agent Problem; Incentive Schemes